Graphene-Based Materials as Solid Phase Extraction Sorbent for Trace Metal Ions, Organic Compounds, and Biological Sample Preparation. (3rd July 2016) - Ibrahim, Wan Aini Wan; Nodeh, Hamid Rashidi; Sanagi, Mohd Marsin
ABSTRACT: Graphene is a new carbon-based material that is of interest in separation science. Graphene has extraordinary properties including nano size, high surface area, thermal and chemical stability, and excellent adsorption affinity to pollutants. Its adsorption mechanisms are through non-covalent interactions (π-π stacking, electrostatic interactions, and H-bonding) for organic compounds and covalent interactions for metal ions. These properties have led to graphene-based material becoming a desirable adsorbent in a popular sample preparation technique known as solid phase extraction (SPE). Numerous studies have been published on graphene applications in recent years, but few review papers have focused on its applications in analytical chemistry. This article focuses on recent preconcentration of trace elements, organic compounds, and biological species using SPE-based graphene, graphene oxide, and their modified forms. Solid phase microextraction and micro SPE (µSPE) methods based on graphene are discussed.